E-Module Development on Hydrocarbon Compounds Material for Class X Agricultural Vocational High School - Sari, Susy Eldila; Susilawati, Susilawati; Anwar, Lenny (FKIP-Universitas Riau, 2021)
The research on the development of e-modules on hydrocarbon compound material for agricultural vocational school education units aims to develop e-modules that are in accordance with the demands of the agricultural vocational curriculum. This study used a research and development (R&D) method with the ADDIE development model which only consists of 3 stages, namely analysis, design and development. The object of research was the e-module on the material of hydrocarbon compounds. The research subjects were 3 educators who taught chemistry subjects at the Agricultural Vocational School and 23 Agricultural Vocational Schools students. Data collection was done through validation sheets and response questionnaires. The results showed that the e-module developed was very valid or very feasible to be tested in the field with an overall average percentage value of material validation of 91.69% and an overall average percentage of media validation of 94.13%. Based on the results of the test, the response of educators obtained an average percentage of 85.18% with the very good category and the results of the students' responses obtained an average percentage of 72.72% with the attractive category. Thus it can be concluded that the e-module of hydrocarbon compounds is very good and interesting to be applied in the learning process on a larger scale.